Reelin Can Modulate Migration of Olfactory Ensheathing Cells and Gonadotropin Releasing Hormone Neurons via the Canonical Pathway - Dairaghi, Leigh; Flannery, Ellen; Giacobini, Paolo; Saglam, Aybike; Saadi, Hassan; Constantin, Stephanie; Casoni, Filippo; Howell, Brian W.; Wray, Susan (Frontiers in Cellular Neuroscience, 2018)
One key signaling pathway known to influence neuronal migration involves the extracellular matrix protein Reelin. Typically, signaling of Reelin occurs via apolipoprotein E receptor 2 (ApoER2) and very low density receptor (VLDLR), and the cytoplasmic adapter protein disabled 1 (Dab1). However, non-canonical Reelin signaling has been reported, though no receptors have yet been identified. Cariboni et al. indicated Dab1-independent Reelin signaling impacts gonadotropin releasing hormone-1 (GnRH) neuronal migration (Cariboni et al., 2005). GnRH cells are essential for reproduction. Prenatal migration of GnRH neurons from the nasal placode to the forebrain, juxtaposed to olfactory axons and olfactory ensheathing cells (OECs), has been well documented, and it is clear that alterations in migration of these cells can cause delayed or absent puberty. This study was initiated to delineate the non-canonical Reelin signaling pathways used by GnRH neurons. Chronic treatment of nasal explants with CR-50, an antibody known to interfere with Reelin homopolymerization and Dab1 phosphorylation, decreased the distance GnRH neurons and OECs migrated. Normal migration of these two cell types was observed when Reelin was co-applied with CR-50. Immunocytochemistry was performed to determine if OECs might transduce Reelin signals via the canonical pathway, and subsequently indirectly altering GnRH neuronal migration. We show that in mouse, 1) both OECs and GnRH cells express ApoER2, VLDLR and Dab1, and 2) GnRH neurons and OECs show a normal distribution in the brain of two mutant reeler lines. These results indicate that the canonical Reelin pathway is present in GnRH neurons and OECs, but that Reelin is not essential for development of these two systems in vivo.